Types of Code Mixing Used by Iman Usman and Faisal Basri in Gita Wirjawan’s Endgame - Donny Indrawan; Herwindy Maria Tedjaatmadja (Institute of Research and Community Outreach - Petra Christian University, 2023)
This study was conducted to analyze the code-mixing types used by Iman Usman as a young adulthood resource person and Faisal Basri as a middle adulthood resource person in Gita Wirjawan’s Endgame, as well as the similarities and differences between the code mixing types used by both respondents. The writers used the theory of code-mixing types by Muysken (2000) and employed a qualitative approach. The findings of this study revealed that both used all the code-mixing types: insertion, alternation, and congruent lexicalization. Content words were also widely found and both Iman Usman and Faisal Basri repeatedly applied the code-mixing with possessed content word (nouns, verbs, adjectives, or adverbs). Moreover, age factor did really affect Iman Usman and Faisal Basri when using code-mixing in their conversation with Gita Wirjawan. Iman Usman used code mixing more often than Faisal Basri.